Artificial Intelligence of things for weather forecasting and climatic behavioral analysis - Gupta, Rajeev Kumar, 1984-; Jain, Arti; Wang, John; Siṃha, Vedaprakāśa; Bharti, Santosh (Advances in computational intelligence and robotics (ACIR) book series., 2022)
"This book provides extensive research for weather forecasting and climatic behavioral prospects that contribute towards detection of weather hazards, mitigation and disaster management through technological enhancement including Machine Learning, Deep Learning, Internet of Things, Artificial Intelligence, Big Data Analytics and Geo-Spatial Visualization"--